(untitled) (Nóema, 2021)
This paper examines cognitive processes from an evolutionary, ecological and systemic perspective. Starting from Darwinian theory and the development of Extended Evolutionary Synthesis, the reference to evolutionary biology allows a rethinking of minds as complex phenomena "at the crossroads" between organisms (and their structures) and the environments they inhabit and contribute to build. It is proposed that this vision opens a space to overcome philosophical traditions that see in the minds "things" and in cognition a mirroring or representation of the world, to come to an understanding of the former in terms of complex systems and to interpret the latter through the concept of "enaction".